Neuropeptide changes persist in spinal cord despite resolving hyperalgesia in a rat model of mononeuropathy. - Munglani, R; Harrison, S; Smith, G; Bountra, C; Birch, P; Elliot, P; Hunt, S (1996)
We have previously described the changes in spinal cord neuropeptides in the unilateral sciatic chronic constriction injury (CCI) model of Bennett and Xie [Pain, 33 (1988) 87-108] at 28 days, a time of maximum mechanical hyperalgesia. In this study we examine the same model 100-120 days post injury by which time resolution of the hyperalgesia and peripheral nerve injury has occurred according to previous studies. Rats underwent either CCI of the sciatic nerve (n = 12) or else sham operation (n = 8) which involved exposure but no ligation of the nerve. Mechanical hyperalgesia was assessed with a Ugo-Basile analgesymeter and immunohistochemistry performed on the spinal cord sections of the animals and quantified using a confocal microscope. At this late time point CCI rats were no longer significantly mechanically hyperalgesic compared to the sham animals (P > or = 0.09). However, examination of the lumbar spinal cord revealed the following changes. (i) The neuropeptides substance P (SP) (P < 0.0001) and galanin (P < 0.003) both showed decreases of about 30% ipsilaterally in immunoreactivity in laminae 1 and 2 of the dorsal horn compared to the sham operated animals. (ii) Calcitonin gene-related peptide (CGRP) and neuropeptide Y (NPY) in laminae 1 and 2 showed no significant changes compared to sham animals. (iii) NPY levels in laminae 3 and 4 of the spinal cord showed a 15% increase in immunoreactivity compared to sham animals (P = 0.008). These results indicate that changes in neuronal markers in the spinal cord can persist after apparent resolution of a peripheral nerve injury. We suggest that these changes may form a substrate for subsequent development of abnormal pain states.